2019
DOI: 10.1111/and.13248
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices and erectile dysfunction: A systematic review and meta‐analysis

Abstract: Elevated platelet levels have been postulated to be associated with cardiovascular diseases, conditions closely linked to erectile dysfunction (ED). The current systematic review and meta‐analysis was performed to assess the platelet indices, which including platelet count (PLT), mean platelet volume (MPV) and platelet distribution width (PDW) in subjects with ED compared to controls in an attempt to clarify the possible role of platelet indices in the pathogenesis of ED. We initially screened the candidate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
9
0
2
Order By: Relevance
“…The relationship between PDW level and the extent of coronary stenosis cannot be identified through a cohort study of a coronary artery patient. (Yang & Muzepper, 2019). The overall results of our meta-analysis showed that the PDW between patients with varicocele and healthy subjects shows no difference, too.…”
Section: Discussionmentioning
confidence: 68%
“…The relationship between PDW level and the extent of coronary stenosis cannot be identified through a cohort study of a coronary artery patient. (Yang & Muzepper, 2019). The overall results of our meta-analysis showed that the PDW between patients with varicocele and healthy subjects shows no difference, too.…”
Section: Discussionmentioning
confidence: 68%
“…A meta-analysis of seven studies including 1319 patients confirmed that patients with ED have higher MPV values than controls and, particularly, patients with vasculogenic ED had significantly higher values compared to both healthy controls and patients with non-vascular ED [31]. A subsequent meta-analysis of 13 studies including 1595 patients with ED and 967 healthy men reached the same conclusion [32].…”
Section: Mean Platelet Volume and Erectile Dysfunctionmentioning
confidence: 70%
“…If by one hand the increase in MPV values in diseases increasing the cardiovascular risk indicates a common underlying pathophysiological mechanism [32], on the other, it is not possible to say whether MPV is a direct risk factor for CAD and ED or only an indirect marker [17]. Indeed, some authors dispute the usefulness of MPV for the early diagnosis of vascular diseases, starting from the assumption that the high MPV is a consequence of the vessel occlusion rather than the cause.…”
Section: Limitsmentioning
confidence: 99%
“…Accordingly, an increasingly higher percentage of platelets expressing the vitronectin receptor (integrin αvβ3) (VR), which is involved in the early phase of platelet aggregation, is associated with lower PSV values in the penile cavernous artery of patients with ED [17]. In addition, meta-analytic data indicate the occurrence of higher MPV values in patients with ED compared to controls [18].…”
Section: Discussionmentioning
confidence: 99%